Efficiency of FeSO4.7H2O as a Coagulant on Chromium Hexavalent Removal Using Coagulation-Flocculation Process: Optimization Using Response Surface Methodology - Pangeran, Andi Baso; Afandy, Moh. Azhar; Sawali, Fikrah Dian Indrawati (Politeknik Negeri Malang, 2023)
Response Surface Methodology-Central Composite Design (RSM-CCD) is widely employed in the process of optimizing the applications of coagulants for wastewater treatment. The experiment aims to evaluate the effect of the FeSO4.7H2O concentration and settling time on removing the chromium hexavalent (Cr (VI)) from wastewater by coagulation-flocculation using RSM-CCD. This experiment was carried out based on the results of the model and optimization using the RSM-CCD to obtain the removal efficiency of Cr (VI) as well as determine the influence of the concentration of FeSO4.7H2O (X1) and settling time (X2). The RSM-CCD experimental design uses a two-factor and two-level design with 13 experimental runs and 5 center points. Inter-variable regression coefficients are also produced with the elimination of Cr (VI). The ANOVA test results showed a fairly significant figure for the assembled model. The model validation results show that the proposed model is compatible with the experimental results. RSM optimization shows optimum conditions based on experimental FeSO4.7H2O coagulant concentration variables and coagulation time at 150 mg/L coagulant concentration and 60 minutes of time, and the prediction results based on RSM-CCD optimization using Design Expert show the most optimum condition at 165,562 mg/L coagulant concentrations and 60,527 minutes of time.